Health-related quality of life in children and adolescents born very preterm and its correlates: a cross-sectional study - Dirk Bassler; Giancarlo Natalucci; Sarah R Haile; Mark Adams; Susi Kriemler; Gabriela P Peralta; Thomas Radtke; Ajay N Bharadwaj; Alexander Moeller (BMJ Publishing Group, 2024)
Objective We aimed to assess health-related quality of life (HRQOL) in a cohort of very preterm born children and adolescents (aged 5-16), and to compare it with their fullterm born siblings and the general population. We also explored correlates of HRQOL among the very preterm born.Design Cross-sectional survey.Patients Children born <32 weeks gestation (N=442) as well as their fullterm born siblings (N=145).Main outcome measures Primary outcome was KINDL total score (0 worst to 100 best), a validated multidimensional measure of HRQOL in children and adolescents.Methods Linear mixed models accounted for family unit. Secondary analysis compared very preterm born children to another cohort of healthy children from the same time period. A classification tree analysis explored potential correlates of HRQOL.Results On average, preterm children, both <28 and 28-31 weeks gestational age, had similar KINDL total score to fullterm sibling controls (−2.3, 95% CI −3.6 to −0.6), and to population controls (+1.4, 95% CI 0.2 to 2.5). Chronic non-respiratory health conditions (such as attention deficit hyperactivity disorder or heart conditions, but not including cerebral palsy), age and respiratory symptoms affecting daily life were key correlates of HRQOL among very preterm born children.Conclusions Very preterm birth in children and adolescents was not associated with a relevant reduction in HRQOL compared with their fullterm born peers. However, lower HRQOL was explained by other factors, such as older age, and the presence of chronic non-respiratory health conditions, but also by possibly modifiable current respiratory symptoms. The influence of respiratory symptom amelioration and its potential influence on HRQOL needs to be investigated further.Trial registration number NCT04448717.